Desi chickpea forage production at different sowing dates and densities - Avalos-Castro, Raúl; Gutierres-Pérez, Erasmo; Melgoza-Villagómez, Claudia María; Osuna-Amador, José Denis; Medina-Córdova, Noé (Revista Mexicana de Ciencias Agrícolas, 2025)
Desi chickpeas are a legume with forage potential due to their high protein and energy content. It has been observed that the sowing date and density affect their yield; however, there is a lack of information to optimize their production under irrigation in arid areas. This study aimed to evaluate the effect of sowing date (October 22, December 22 and January 22), sowing density (27, 41 and 55 kg ha-1), and Desi chickpea varieties (El Patrón, Pénjamo, and San Antonio 05) on forage yield (FY), grain yield (GY), and harvest index (HI). The experimental design used was randomized complete blocks arranged in subsplit plots and three replications, the experiment was replicated in two agricultural cycles (2018-2019 and 2019-2020). The data were analyzed by means of an analysis of variance, with comparison of means using mutually orthogonal contrasts. The sowing date of December 22 favored FY and GY with values of 12.9 and 3.5 t ha-1. The density of 27 kg ha-1 excelled by achieving values of 11.4 t ha-1, 3.41 t ha-1, and 32.65% in FY, GY, and HI. The best variety in FY was El Patrón with 12 t ha-1, while San Antonio 05 stood out in GY and HI with values of 3.4 t ha-1 and 34.8%. This study highlights the importance of defining an optimal level in the factors evaluated for their influence on the yield of Desi chickpea varieties under irrigated conditions.
Keywords: Cicer arietinum L.; chickpea straw; forage yield; ruminant nutrition